Antidepressant-Like Effects of Fractions Prepared from Danzhi-Xiaoyao-San Decoction in Rats with Chronic Unpredictable Mild Stress: Effects on Hypothalamic-Pituitary-Adrenal Axis, Arginine Vasopressin, and Neurotransmitters. (20th June 2016) - Wu, Li-Li; Liu, Yan; Yan, Can; Pan, Yi; Su, Jun-Fang; Wu, Wei-Kang
Abstract : The aim of the present study was to investigate the antidepressant-like effects of two fractions, including petroleum ether soluble fraction (Fraction A, FA) and water-EtOH soluble fraction (Fraction B, FB) prepared from the Danzhi-xiaoyao-san (DZXYS) by using chronic unpredictable mild stress-induced depressive rat model. The results indicated that DZXYS could ameliorate the depression-like behavior in chronic stress model of rats. The inhibition of hyperactivity of HPA axis and the modulation of monoamine and amino acid neurotransmitters in the hippocampus may be the important mechanisms underlying the action of DZXYS antidepressant-like effect in chronically stressed rats.